2008
DOI: 10.1016/j.foodchem.2008.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ginsenosides in Panax ginseng in high pressure microwave-assisted extraction

Abstract: High pressure microwave assisted extraction (HPMAE) was applied to extract the ginsenosides from Panax ginseng root. The influences of extraction solvent, extraction pressure and extraction time were individually investigated. HPMAE has been compared with other extraction methods, including Soxhlet extraction, ultrasound-assisted extraction and heat reflux extraction. The determination of ginsenosides was performed by HPLC-ESI-MS. The results indicated that the HPMAE not only took a shorter time but also affor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(59 citation statements)
references
References 25 publications
5
52
1
1
Order By: Relevance
“…Similar to this result, Wang et al (35) also found that the increase in the extraction yield was very small as a function of time in microwave extraction. The reason for the insignifi cant increase could be explained by the fact that MASE of diff erent compounds is usually completed within a few minutes to half an hour, depending on the extracted material as mentioned in literature (33,(36)(37)(38).…”
Section: Timesupporting
confidence: 71%
“…Similar to this result, Wang et al (35) also found that the increase in the extraction yield was very small as a function of time in microwave extraction. The reason for the insignifi cant increase could be explained by the fact that MASE of diff erent compounds is usually completed within a few minutes to half an hour, depending on the extracted material as mentioned in literature (33,(36)(37)(38).…”
Section: Timesupporting
confidence: 71%
“…A longer extraction time tends to improve the extraction yield. However, extraction effi ciency is insignifi cant with longer time (Wang et al, 2008b). A solvent can infl uence the TPC Various lowercase letters in the same row denote signifi cant diff erence (p < 5%) between microwave powers.…”
Section: Eff Ect Of Extraction Time On Extraction Of Phenolic Compoundsmentioning
confidence: 99%
“…34 Ginsenoside was extracted from Panax Ginseng C.A Meyer root (collected from Medicinal Plants and Drugs Research Institute, Shahid Beheshti University, Iran) using the Soxhlet method. 14 Briefly, 1.000 g powder of the clean root (weighted in a cellulose cartridge) was extracted in Soxhlet with 95 ml of dichloromethane for a 60 min boiling, 15 min rinsing and 45 min drying periods.…”
Section: Panax Ginseng Ca Meyer Root Extraction and Characterizationmentioning
confidence: 99%